2016
DOI: 10.13005/bbra/2096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eCG in Milking Dairy Cows with High Levels of BUN and Synchronized with Ovsynch Protocol

Abstract: Previous research indicates that high blood urea nitrogen (BUN) concentrationsare associated with decreased fertility in lactating dairy cows.This experiment was done to evaluate the effects of equine chorionic gonadotropin (eCG) administration (with or without eCG) on fertility of lactating dairy cows with different levels of BUN subjected to fixed-time artificial insemination (FTAI).Ovulation was synchronized in all cows using Presynch-Ovsynch program and start 37 days post parturition(pp). Blood samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…(5) Findings of a study showed that serum concentrations of P4 were increased significantly on day 5 post insemination in cows that received 600 IU eCG at the time of PGF2α injection in the Ovsynch protocol compared to the cows that did not receive eCG at the mentioned time. (44) It was demonstrated in a study that injection of 400 IU eCG at the time of the last PGF2α injection in the Presynch-Ovsynch protocol increased the number of CLs on the ovaries compared to the cows that did not receive eCG at this time. (45) Various studies have highlighted the positive effects of high serum concentrations of P4 in the luteal phase before insemination to increase pregnancy rates in cows.…”
Section: Resultsmentioning
confidence: 99%
“…(5) Findings of a study showed that serum concentrations of P4 were increased significantly on day 5 post insemination in cows that received 600 IU eCG at the time of PGF2α injection in the Ovsynch protocol compared to the cows that did not receive eCG at the mentioned time. (44) It was demonstrated in a study that injection of 400 IU eCG at the time of the last PGF2α injection in the Presynch-Ovsynch protocol increased the number of CLs on the ovaries compared to the cows that did not receive eCG at this time. (45) Various studies have highlighted the positive effects of high serum concentrations of P4 in the luteal phase before insemination to increase pregnancy rates in cows.…”
Section: Resultsmentioning
confidence: 99%